2018
DOI: 10.1371/journal.pntd.0006749
|View full text |Cite
|
Sign up to set email alerts
|

Community-based prevalence of typhoid fever, typhus, brucellosis and malaria among symptomatic individuals in Afar Region, Ethiopia

Abstract: BackgroundIn sub-Saharan Africa, where there is the scarcity of proper diagnostic tools, febrile illness related symptoms are often misdiagnosed as malaria. Information on causative agents of febrile illness related symptoms among pastoral communities in Ethiopia have rarely been described.MethodsIn this a community based cross-sectional survey, we assessed the prevalence of typhoid fever, typhus, brucellosis and malaria among individuals with a set of given symptoms in Amibara district, Afar Region, Ethiopia.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
41
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 34 publications
9
41
4
Order By: Relevance
“…By extrapolation, the overall prevalence of Salmonella infection was 7.70%. These data are more or less similar to the previous findings of two independent studies from Ethiopia and Nigeria [ 29 , 30 ] but is much lower than the extent of prevalence described by some other authors in Ethiopia [ 32 , 33 ]. Nevertheless, the rate of Salmonella infection currently observed was relatively lower than S. mansoni infection, and almost all Salmonella -infected patients were positive for S. mansoni , considering both health institutions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…By extrapolation, the overall prevalence of Salmonella infection was 7.70%. These data are more or less similar to the previous findings of two independent studies from Ethiopia and Nigeria [ 29 , 30 ] but is much lower than the extent of prevalence described by some other authors in Ethiopia [ 32 , 33 ]. Nevertheless, the rate of Salmonella infection currently observed was relatively lower than S. mansoni infection, and almost all Salmonella -infected patients were positive for S. mansoni , considering both health institutions.…”
Section: Discussionsupporting
confidence: 91%
“…Male patients ( n = 38) outnumbered female patients; this is in agreement with the findings of previous studies conducted in another region of Ethiopia [ 28 ] and also Sudan [ 27 ]. It was also found that a majority (n = 31) of positive cases occur in children aged 5 to 15; this finding is by and large consistent with the data in the existing literature [ 29 , 30 ]. A possible reason for the higher prevalence rate of S. mansoni in children might be attributed to their frequent recreational activities in muddy, contaminated and stagnant water bodies, which are laden with snails infected with S. mansoni .…”
Section: Discussionsupporting
confidence: 89%
“…Camel seropositivity for brucellosis in Ethiopia ranged from 0.7 to 12% for the Rose Bengal Plate Test (RBPT) and 0.5 −10% for Complement Fixation Test (CFT) in different agro-ecologies [14]. Studies on human brucellosis in Ethiopia are sparse with less information about risk factors for human infection [13, 17].…”
Section: Introductionmentioning
confidence: 99%
“…A health institution based cross-sectional study design was used to determine sero-prevalence and risk factors of brucellosis among febrile patients visiting health institutes of Awra and Gulina district of Afar region, Ethiopia from February to May 2019. The nding of previous community based sero-prevalence of brucellosis (4.4%) in other pastoral area of the community of the region was used to estimate the sample size [17]. Based on this information, the calculated sample size, at 95% con dence level, 5% degree of accuracy and with 10% compensation for refusal, was 444 respondents.…”
Section: Study Design and Sample Size Determinationmentioning
confidence: 99%
“…Some studies have showed that animal brucellosis is highly distributed and the livelihood of the population is very close to animals that create potential risk factors to acquire brucellosis [13][14][15]. Nevertheless, human brucellosis has been rarely surveyed either as misdiagnosed or abandoned at all due to similarity of signs and symptoms presumably with malaria or unfamiliarity of health care workers with the disease and its epidemiology in this area [16,17]. The aim of this study was to determine the sero-prevalence and risk factors of human brucellosis among febrile patients visiting health institutes in Awra and Gulina District of Afar region, Ethiopia…”
Section: Introductionmentioning
confidence: 99%